2010
DOI: 10.1017/s0950268810000063
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for Japanese encephalitis: a case-control study

Abstract: Japanese encephalitis (JE) has been found to be endemic in Bali, Indonesia. A case-control study was conducted to identify factors associated with JE infection. All 94 serologically confirmed JE cases (cases) and 163 cases of encephalitis or aseptic meningitis without JE (controls) identified in Bali during 2001-2004 were included in the study. Potential risk factors were surveyed at hospital admission. Univariate analyses revealed the following factors to be associated with JE: older age, referral from sub-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 16 publications
2
38
1
2
Order By: Relevance
“…The literature indicated that pigs play a central role in the transmission of both the Japanese encephalitis virus and cysticercosis [18]. Expansion of the JE virusendemic area depends on irrigated rice farming and pig rearing [3]. A higher proportion of rice planting could, therefore, predict a higher risk of JE [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature indicated that pigs play a central role in the transmission of both the Japanese encephalitis virus and cysticercosis [18]. Expansion of the JE virusendemic area depends on irrigated rice farming and pig rearing [3]. A higher proportion of rice planting could, therefore, predict a higher risk of JE [19].…”
Section: Discussionmentioning
confidence: 99%
“…Humans are incidental or dead-end hosts because they usually do not develop a level or duration of viremia sufficient to infect mosquitoes. Culex tritaeniorhynchus, the major mosquito vector, breeds by laying eggs in rice fields, and the pig is considered the most common amplifying host of the JE virus [3]. An estimated 67,900 JE cases typically occur annually, of which only 10% are reported to the World Health Organization [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beberapa faktor penentu kejadian penyakit JE di Indonesia karena interaksi induk semang dengan vektor (Liu et al 2010). Penyebaran virus JE sangat tergantung oleh beberapa faktor, antara lain binatang perantara seperti babi, kera, burung dan vektor (nyamuk).…”
Section: Mekanisme Penularan Virus Japanese Encephalitisunclassified
“…Berdasarkan laporan hasil surveilans berbasis rumah sakit di enam provinsi pada tahun 2005-2006, disimpulkan bahwa JE telah endemis di Indonesia dengan persentase positif antibodi terhadap JE antara 1,8 hingga 17,9% (Ompusunggu et al 2008). Pulau Bali merupakan salah satu daerah endemis JE, terutama di musim hujan (Kari et al 2006;Liu et al 2010). Kasus JE pada manusia di Indonesia telah ditemukan di 17 provinsi hingga tahun 2006.…”
Section: Infeksi Virus Japanese Encephalitis DI Indonesiaunclassified